2012
DOI: 10.3892/ijmm.2012.1096
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits HCV replication by induction of heme oxygenase-1 and suppression of AKT

Abstract: Although hepatitis C virus (HCV) affects approximately 130–170 million people worldwide, no vaccines are available. HCV is an important cause of chronic hepatitis, cirrhosis and hepatocellular carcinoma, leading to the need for liver transplantation. In this study, curcumin, a constituent used in traditional Chinese medicine, has been evaluated for its anti-HCV activity and mechanism, using a human hepatoma cell line containing the HCV genotype 1b subgenomic replicon. Below the concentration of 20% cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 63 publications
4
40
0
1
Order By: Relevance
“…In addition, many natural products show significant cytoprotective effects in various diseases as well as that GSE have been studied and showed significant effects in many disease, including cancer, inflammation, and even infectious diseases. Comparable with present study, there are several compounds which have significant antioxidant activity against HCV infection, such as curcumin, silymarin, silibinin, and epigallocatechin-3-gallate (EGCG) (Chen C. et al, 2012; Chen M.H. et al, 2012; Polyak et al, 2013).…”
Section: Discussionsupporting
confidence: 49%
“…In addition, many natural products show significant cytoprotective effects in various diseases as well as that GSE have been studied and showed significant effects in many disease, including cancer, inflammation, and even infectious diseases. Comparable with present study, there are several compounds which have significant antioxidant activity against HCV infection, such as curcumin, silymarin, silibinin, and epigallocatechin-3-gallate (EGCG) (Chen C. et al, 2012; Chen M.H. et al, 2012; Polyak et al, 2013).…”
Section: Discussionsupporting
confidence: 49%
“…In human cells, HO1 can inhibit the replication of viruses such as HIV (40), Ebola (59) and HCV (60). However, a direct role for HO1 in human macrophages infected with Mtb infection has not previously been established.…”
Section: Discussionmentioning
confidence: 99%
“…Viral entry into both hepatoma cell lines as well as PHHs was inhibited by the presence of the compound without affecting the viability of the cells. Using reporter replicon, it has been reported that curcumin can inhibit HCV subgenomic RNA replication 38 39. However, the activity of the reporter gene was inhibited by only 50% at 15 µM, and RNA levels reduced to only ∼55% at 20 µM.…”
Section: Discussionmentioning
confidence: 99%